Metadiscourse markers in Malaysian undergraduate essay corpus. - Amaal Fadhlini Mohamed (2019)
Metadiscourse is used by a writer to organise his text and textually interact with the potential readers. An effective use of metadiscourse reflects the writer’s writing ability because it is one of the aspects in composing process of making a successful text. However, ESL writers especially undergraduates tend to face problems in using metadiscourse markers in their writing. Many of them do not use the metadiscourse markers appropriately in their essay writing. Employing social cognitive theory of writing as its theoretical framework, this corpus-based study investigated the use of metadiscourse markers in Malaysian undergraduate essays written by undergraduates from a public university in Malaysia. Of particular interest, this study investigated how the use of metadiscourse has affected the flow of the essay content and quality as a whole. The corpus examined in the study was built from 195 persuasive essays written by the second year undergraduate writers at the university. The corpus was divided into two main corpora of good and weak essays and further extracted to build two other subcorpora of the best essays (BESS sub-corpus) and weakest essays (WESS sub-corpus). The metadiscourse markers in the essays were searched with the assistance of a concordance software, WordSmith Tools. The use of metadiscourse in the two main corpora of good essays (TOGOOD corpus) and weak essays (TOWEAK corpus) was compared and contrasted. The quantitative analysis of the corpus shows that organisational discourse markers were more frequently used compared to interpersonal discourse markers. More metadiscourse items (based on occurrence per 1, 000 words) were found in weak essays (TOWEAK corpus) as compared to good essays (TOGOOD corpus). The TOGOOD and TOWEAK corpora show a higher frequency of use in organisational discourse markers category as compared to interpersonal discourse markers category. More types of metadiscourse were found in good essays (TOGOOD corpus and BESS sub-corpus) as compared to weak essays (TOWEAK corpus and WESS sub-corpus). Meanwhile, the qualitative analysis shows that writers of both subcorpora (i.e BESS and WESS) have almost equal awareness in using metadiscourse markers. They have distinctive invention of metadiscourse markers with innovative new phrases or markers which were made up to suit the purpose of the text. Some of the markers are grammatically inappropriate and wrongly spelled. Although the undergraduate writers are aware of using metadiscourse markers in their essays, there are misconception found in both good essays and weak essays such as the marker ‘then’ is often misunderstood as ‘than’ in comparison. This study concludes that the best essays corpus demonstrates a greater use of metadiscourse markers in the right context. Therefore the undergraduate writers need to be trained on how to use both metadiscourse categories (organisational and interactional discourse markers) appropriately so that they can further develop their writing skills.